2019
DOI: 10.20518/tjph.449674
|View full text |Cite
|
Sign up to set email alerts
|

A study of the frequency of overweight, obesity and metabolic syndrome among university students

Abstract: The aim of this study was to assess the frequency of excess weight, obesity and other metabolic syndrome components among university students. Methods: This cross-sectional study included a total of 357 university students. The socioeconomic data, lifestyle, and cardiovascular disease risk factors were filled out using a questionnaire. The clinical screenings included measurement of blood pressure and determination of fasting lipid and glucose concentrations. T-test, Pearson Chi-Square and Fisher's Exact Test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 10 publications
5
1
0
Order By: Relevance
“…The present study demonstrated that the prevalence of MetS was higher in males compared to females and males were 3.4 times more likely to develop MetS than females, which is statistically significant. This result agreed with several previous students' studies (10,12,26,34). The higher prevalence of MetS in males can be related to excess body weight, sedentary lifestyles such as physical inactivity and a higher rate of smoking.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The present study demonstrated that the prevalence of MetS was higher in males compared to females and males were 3.4 times more likely to develop MetS than females, which is statistically significant. This result agreed with several previous students' studies (10,12,26,34). The higher prevalence of MetS in males can be related to excess body weight, sedentary lifestyles such as physical inactivity and a higher rate of smoking.…”
Section: Discussionsupporting
confidence: 93%
“…A study observed the same outcome that smokers were 6 times more likely to exhibit MetS (10). The same finding also concurred with the present study outcome that smoking habit has a significant association with MetS (12). In contrast, a study on Egyptian students, and a study on Palestinian students observed no significant relationship between smokers and MetS (32,40).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations